THE METHODOLOGICAL FOUNDATIONS FOR DEVELOPING REFLECTIVE THINKING IN THE EDUCATIONAL PROCESS - Odiljanova, Gulasalxon (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
In this thesis, reflective thinking is interpreted as a meta-competence that ensures the quality and sustainability of the educational process, and methodological foundations are developed to promote its enhancement. Based on scientific and theoretical sources, the content and essence of the concept of reflection are illuminated, and a system of didactic strategies applicable at the stages of planning, executing, and assessing educational activities is organized. The research proposes an integrative model for the use of lesson scenarios, reflective journals, metacognitive questions, peer feedback, digital portfolios, and analytical rubrics based on an experiential-didactic approach. The discussion substantiates the role of the reflective cycle (experience–analysis–conceptualization–testing) in creating personalized learning trajectories for students and in fostering a culture of decision-making in problematic situations. The conclusions outline the conditions for the effectiveness of the methodology, assessment criteria, and mechanisms to support teachers' professional reflection.